Variasi Genetik Gen Penyandi Protein Fusi dari Avian Paramyxovirus Tipe I di Bali (GENETIC VARIATION OF GENE ENCODING FUSION PROTEIN OF AVIAN PARAMYXOVIRUS TYPE-I IN BALI - Putra, I Gusti Agung Arta; Adi, Anak Agung Ayu Mirah; Astawa, Nyoman Mantik (Jurnal Veteriner; Vol 17 No 2 (2016), 2016)
This study aims to determine the genetic variation of gene encoding fusion (F)-protein of avianparamyxovirus (APMV) type-1 isolated from chickens suffering of Newcastle disease (ND) found in achicken farm in the province of Bali throughout the year 2014. There are five isolates got from sick chickenscases/death suspected of being infected by APMV -1, but negative for avian influenza virus (AIV) infectioni.e: D5/AK/2014, B1/AK/2014, T1/ARP/2014, G1/AK/2014, and K1/ARP/2014. Sequence analysis of thefive isolates showed that three isolates of D5, B1 and G1 have a genetic distance of 11,1%, 10,2% and 8,2%when compared to the nucleotide sequence of Bali-1/07 isolated previously from Karangasem regency in2007. Meanwhile, the genetic distance of T1 and K1 isolates are 20,1% and 18% respectively as compareto the sequence of the Bali-1/07 isolate. The composition of amino acids at the cleavage sites enzyme of Fproteinfor 3 isolates of D5, B1 and G1 are R-R-Q- K-R-F, which is the typical characteristic of virulentvirus strain. Meanwhile, two isolates i.e T1 and K1 got from layer chicken had the amino acid sequence ofG- R-Q-G -R-L, which is group into avirulent virus strains. It was concluded that APMV-1 isolates foundin ND cases in the year of 2014 were caused by virulent isolate and were grouped into VII-genotype.Furthermore, It was found that there were two avirulent isolates
Keywords: avian paramyxovirus type 1; F-protein gene; ND; genetic distance